(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The 1993 Minsk Convention and the 2002 Chisinau Convention on Legal Assistance and Legal Relations in Civil, Family and Criminal Matters form the principal treaty framework for cooperation among the CIS member states. Through these mechanisms, service of documents, execution of procedural requests, taking of evidence, and the recognition and enforcement of judicial acts in cases involving a foreign element are ensured.